ДИЛОРОМ АБДУРАҲМОН ШЕЪРИЯТИДА ОШИҚ ВА ИШҚ ТАЛҚИНИ - Жумаева, С. (SCIENCE and SOCIETY, 2024)
The article discusses about the poetic world of Faxriyor’s poetry, which has entered Uzbek poetry with new ways of expression, new poetic thinking, no unexpected metaphors.